Bibliometrics Analysis Of The Resistance Of Steel Materials In Building Structures To Fire - Rizqi Valiant; Andri Irfan Rifai; Usmanul Hayadi Umar; Muhammad Isradi (Journal of Social Research, 2024)
Fire is the out-of-control burning method of flammable substances, which includes wood, paper, plastic, fuel, or different substances, which produce heat, mild smoke, and toxic gases. Fires can occur, including woodland fires caused by lightning or because of human activities, along with building fires due to electric short circuits or errors in the use of fire. In building design, it is miles vital to apprehend the elements that cause fires and the fireplace's resistance to materials. Metal is a form of metallic made from a primary mixture of iron (Fe) and carbon (C), with the amount of carbon typically being much less than 2 per cent of its general weight. Steel is a very common fabric used in a spread of applications due to its aggregate of robust, long-lasting, and malleable properties.